Specific features of antagonism of Bacillus bacteria against toxinogenic Fusarium fungi in protecting plants against disease and contamination with mycotoxins (review) - T. M. Sidorova; A. M. Asaturova; V. V. Allakhverdyan (Юг России: экология, развитие, 2022)
Aim. Summarize and analyze information on the results of studies on the antagonistic properties of Bacillus bacteria against phytopathogenic fungi of the genus Fusarium.Materials and Methods. Current information of research by Russian and foreign scientists on the role of bacteria of the genus Bacillus to suppress Fusarium diseases of plants and contamination of plant products with mycotoxins was studied and critically analysed.Results. Information on the prospects for the use of bacteria‐antagonists of phytopathogenic fungi of the genus Bacillus for plant protection against diseases caused by toxinogenic fungi of the genus Fusarium has been generalized. The role of lipopeptides produced by bacteria in inhibiting the growth of fungi, which manifests itself both through the destruction of the cell wall of the fungus and by increasing the immune status of the plant, has been shown. The study contains information on the structure and mechanism of action of the main anti‐fungal cyclic lipopetides. The features of the manifestation of the antagonistic properties of Bacillus bacteria, which consist in the ability of bacterial metabolites to destroy mycotoxins which can help to reduce their toxicity, have been disclosed. The prospect of searching for bacterial strains of the genus Bacillus suitable for creating effective biofungicides against Fusarium fungi is substantiated.Conclusion. Knowledge of the mechanisms of action of bacteria of the genus Bacillus as antagonists of Fusarium fungi will contribute to the careful selection of strains that are promising for the development of effective biological products for replacing chemical fungicides with biofungicides in the control of F. graminearum and its mycotoxins, which will make it possible to obtain products that are not burdened with either chemical means of protection or mycotoxins which are dangerous for consumers.